Pelatihan Manajemen Tentang Badan Usaha Milik Desa Bagi Perangkat Desa Dan Kelompok Kerja - Dianawati Suryaningtyas (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
Badan Usaha Milik Desa (BUMDes) is a government program aims to build community welfare through independent economic. To build BUMDes is obligated to all district which has been given socialization dan training about this enterprise by local government. This community service was conducted in Pakisjajar aims to helpÃ¢â‚¬Âperangkat desaÃ¢â‚¬Â and Ã¢â‚¬Å“kelompok kerja (Pokja)Ã¢â‚¬Â with management knowledge in oder to build BUMDes. The result of training showed that all participants antusiastic by asking many questions and discussing their problems. As the training ended, all participants stated that they satisfied with the material of training. It was complete and met their needs and they felt sure to build BUMDes. Hopefully, participants of this training can build BUMDes as soon as possible and can manage the enterprise succesfully.